Dysmenorrhea and recent treatment options in adolescents and young adults - Innocent Rani , Vanitha; Dash, Biswajit; Nancy Lal, Monica; P, Muthu Prasanna; Bagchi, Sovan; Aruna, V.; Prabha, K. Suria (Universa Medicina, 2024)
Dysmenorrhea, or primary dysmenorrhea (PD), marked by menstrual cramps in the lower abdomen, is a common but often overlooked condition affecting a considerable number of women. The impact of dysmenorrhea extends beyond physical pain, often causing considerable disruption to daily activities, work, and social interactions. It significantly affects the quality of life, often causing absenteeism from school or work. Increased intrauterine prostaglandin secretion is linked to pelvic pain in PD. Diagnosis relies mainly on clinical assessment, considering symptoms and physical examination, with treatment aimed to enhance the quality of life. These menstrual cramps are frequently accompanied by other symptoms, such as headaches and nausea, which are believed to be due to prostaglandins released as the endometrium breaks down. A literature search using the keywords dysmenorrhea, menstrual pain, and hormonal contraceptives was done using the following databases: Google Scholar, ProQuest, ScienceDirect, Web of Science, Pubmed, and Scopus for articles published  from   2015 to 2024. The literature study was done to find the connection of dysmenorrhea and menstrual pain with hormonal contraceptives. Common treatments include nonsteroidal anti-inflammatory drugs, hormonal contraceptives, and non-pharmacological interventions. This review provides an in-depth analysis of recent treatment advancements for dysmenorrhea, focusing on its pathophysiology, clinical diagnosis, and impact on women's quality of life. It evaluates current and emerging treatments, including pharmacological interventions, non-pharmacological therapies, surgical approaches, hormonal treatments, and investigational drugs, aiming to identify improvements in efficacy and side effects.